Using Oral Anticoagulant During the Covid-19 Pandemic in Albania - Dama, Aida (European Journal of Multidisciplinary Studies, 2023)
The COVID-19 pandemic is a global health situation characterized by a highly infectious respiratory illness caused by the novel coronavirus SARS-CoV-2. From the first burst until nowadays, the virus had a significant impact on global public health and economies, leading to widespread lockdowns, disruptions to daily life, and a significant number of hospitalizations and deaths. Therapy for COVID-19 primarily involved supportive care, such as supplemental oxygen and hydration, to help alleviate symptoms and prevent complications. Antiviral medications, such as remdesivir, and corticosteroids, such as dexamethasone were also used. With the advancing of the disease, it was seen that the disease attacked the blood vessels and clot formation was a major deadly side effect of the virus. The usage of anticoagulants became priority as they could help in reducing of the risk of thrombosis and other complications associated with the virus. In this study we present a brief summary regarding increase in the usage of oral anticoagulants’ usage among Albanian population in a time slot of four years. The new virus was strongly associated and characterized with clot manifestation in the COVID-19 positive patients. The use of anticoagulants in COVID-19 is important because the virus was associated with a higher risk of thrombotic events, including deep vein thrombosis (DVT), pulmonary embolism (PE), and stroke.